Realization and transport investigation of a single layer-twisted bilayer graphene junction. (15th August 2020) - Rui, Dingran; Sun, Luzhao; Kang, N.; Li, Jiayu; Lin, Li; Peng, Hailin; Liu, Zhongfan; Xu, H.Q.
Abstract: We report on realization and low-temperature transport study of a single layer graphene (SLG)-twisted bilayer graphene (tBLG) junction device. The SLG-tBLG junction in the device is grown by chemical vapor deposition and the device is fabricated in a Hall-bar configuration. The longitudinal resistances across the SLG-tBLG junction (cross-junction resistances) on the two sides of the Hall bar are measured. In the quantum Hall regime, the measurements show that the measured cross-junction resistances exhibit a series of new quantized plateaus and the appearance of these resistance plateaus can be attributed to the presence of the well-defined edge-channel transport along the SLG-tBLG junction interface. The measurements also show that the difference between the cross-junction resistances measured on the two sides of the Hall-bar provides a sensitive measure to degeneracy lifting of the Landau levels in the tBLG layer. Temperature dependent measurements of the cross-junction resistance are also carried out and the influence of the transverse bulk transport on the edge channel transport along the SLG-tBLG junction interface are extracted. These results enrich the understanding of the charge transport across interfaces in graphene hybrid structures and open up new opportunities for probing exotic quantum phenomena in graphene devices. Graphical abstract: Image 1